FAKTOR DETERMINAN AYAH YANG BERHUBUNGAN DENGAN PRAKTIK ASI EKSKLUSIF DI WILAYAH KERJA PUSKESMAS GAYAMSARI KOTA SEMARANG - Himma Sahulika; Dina Rahayuning Pangestuti; M. Zen Rahfiludin (Jurnal Kesehatan Masyarakat (Undip), 2017)
Exclusive breastfeeding for 6 months is the optimal way of feeding infants, there after infants should receive complementary foods with continued breastfeeding up to 2 years of age or beyond. Exclusive breastfeeding affected by internal and external factors on the mother as father’s support. Various studies indicate father’s knowledge and attitude are associated with exclusive breastfeeding. In addition parity is also associated with exclusive breastfeeding practice. This study aimed to knew father’s determinant factors wich associated with exclusive breastfeeding practice.This research is done in the Puskesmas Gayamsari working area which aims to find out the father’s determinant factors who influence to exclusive breastfeeding practice. The research design used was Cross Sectional. The population and samples are couples who have babies aged 0-6 months. At the beginning of research samples are grouped into non exclusive breastfeeding and exclusive breastfeeding. Samples are obtained by using purpossive sampling tachniques. Data were colected by interview using a questionnaire and analyzed with univariate and bivariate analysis. Result showed there was significant correlation between father’s knowledge, father’s attitude and parity with exclusive breastfeeding practices. Age, education, occupation, and income as the variables from father (father’s characteristic) is not related to exclusive breastfeeding practice. This research recommend that healthcare professional to increase education about exclusive breastfeeding through outreach and angage fathers in pregnant women class so that father’s support to exclusive breastfeeding would be increased.